Cooperative communications for improved wireless network transmission framework for virtual antenna array applications - Uysal, Murat, 1973- (Information Science Reference, 2010)
"This book provides readers with a comprehensive understanding of the fundamental principles of cooperative communications with a particular emphasis on physical layer issues and further presents the latest advances and open research problems in the wireless network field"--Provided by publisher.